The Red Mist? Red Shirts, Success and Team Sports - Marco Piatti; David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Baron von Richthofen (the Red Baron) arguably the most famous fighter pilot of all time painted his plane the vividest of red hues, making it visible and identifiable at great distance, showing an aggressive pronouncement of dominance to other pilots. Can colour affect aggression and performance and if so is it observable within team sports? This study explores the effect of red on sporting performances within a team sports arena, through empirical analysis of match results from the Australian Rugby League spanning a period of 30 years. While the descriptive analysis reports a positive relationship, the multivariate analysis provides some mixed results once you control for team effects. Thus, more evidence at the team level is required to better understand whether teams in red do enjoy greater success controlling explicitly in a multivariate analysis for many factors that simultaneously affect performance.
Keywords: A12; Z00; 330; impact of team colours; red; (Australian) rugby league; team sports